Improving the protection of intellectual property for audio files using watermarking - يونس, علي; حسن خضور (Latakia University Journal -Engineering Sciences Series, 2025)
Digital watermark has become an effective technology in the field of multimedia intellectual property protection, which means embedding a digital signal or pattern such as a text document, image, audio file, etc. within the original signal. The added file carries private information of the copyright owner or creator of the document to protect his ownership and prove that he created the digital file. In this study, we included a digital watermark as a special image within an audio signal, and this mark is the Quick Response Code. The watermark was embedded in the audio file at the least significant bit (LSB) and the basic parameters of the resulting signal were compared under a set of scenarios on a set of audio files. These parameters include peaks-to-noise ratio (PSNR), signal-to-noise ratio (SNR) and mean squared error (MSE).